Cointegration and causality between overnight policy rate and commercial bank rate / Abdul Razak Jambari, Azizah Daut and Noranita Abdamia - Jambari, Abdul Razak; Daut, Azizah; Abdamia, Noranita (2012)
Monetary economics theory suggests that certain commercial bank rate variables should be linked by a long-run equilibrium relationship. Although the commercial bank rate may drift away from equilibrium for a while, government actions may be expected to restore equilibrium. The purpose of this study is to investigate the cointegration and causal relationship between Overnight Policy Rate (OPR) and the commercial bank rate Conventional bank rate and Islamic bank rate). The evidence generally supports the existence of long run relationship between the variables.